Measuring body composition of primigravida females with Bioelcetrical impedence analysis- a Randomized Control Trial - Tariq, Kalsoom; Khan, Hashim; Inayat, Bela; Zafar, Hafsa; Sher, Nabila (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVE: To evaluate body composition changes (body mass, bone mass, fat mass, hydration, and BMI) during pregnancy in primigravida using bioelectrical impedance analysis. METHODOLOGY: A total of 40 primigravida females were included in a single‑blinded randomized controlled trial conducted in the tertiary care hospitals of KPK. They were further divided into a placebo and lipid based nutritional supplement (LNS)group of 20 each from ≤12 weeks’ gestation (first antenatal checkup). Sample size calculation was done using OpenEpi ®software. Whole‑body composition was measured with a foot‑to‑foot eight‑electrode, single-frequency bioelectrical impedance analysis (BIA) scale (50 kHz reference) at ≤12 weeks (V1), 16-20 weeks (V2) and postnatally (V3). Data were analyzed using IBM SPSS Statistics (version 20). Repeated‑measures ANOVA was used to assess time effects and within-group effects. (α = 0.05). RESULTS: Across both groups, a significant time effect was observed for weight (F = 36.3, p < 0.001; η² = 0.51), BMI (F = 44.8, p < 0.001; η² = 0.57). Mean weight (F = 3.180, p < 0.048; η² = 0.086) and bone mass estimate (F = 3.63, p = 0. 05; η² = 0.096) differed between the supplement and placebo groups. Fat mass and hydration displayed the expected trimester-specific trends but did not reach statistical significance after correction. CONCLUSION: BIA showed reliable changes in weight, BMI, and bone mass during pregnancy. When properly used, it can be a useful tool in routine antenatal settings, especially where resources are limited.